Phylodinamics of papaya ringspot virus on carica papaya L in Cuba - Cabrera Mederos, Dariel (2021)
Papaya is broadly cultivated in tropical and subtropical regions. However, they are affected by the Papaya ringspot virus (PRSV), which is the most economically important virus affecting papaya worldwide. This study aimed to determine the phylodynamics of PRSV on papaya in Cuba. For this purpose, orchardand garden papaya crops grown in 47 Cuban municipalities were surveyed from 2008 to 2013, revealing thewidespread distribution of PRSV in Cuba. Phylodynamic analyses performed with the coat protein partial geneof all Cuban PRSV-P isolates (34 sequences) and 107 sequences of isolates from the American continent and theCaribbean islands showed a most recent common ancestor in 1942 (HPD95 % = 1911- 1967). The substitutionrate was estimated to be 7.7 × 10-4 substitutions per site per year (HPD95 % = 4.6 × 10-4-1.1 × 10-3), whichis equivalent to those detected in other RNA viruses. Demographic reconstruction of PRSV showed that viraldiversity increased in the 1985-1990 period, which coincides with the implementation of extensive productionpractices. Moreover, in Cuba viral dispersion introductions were observed to occurre from Mexico and otherunknown ancestral localization. The spatio-temporal diffusion analysis proposed Mexico as an ancestral area forthe origin of diversification in the American continent and suggests new dispersion events between Americanand Caribbean isolates. The observed widespread distribution, clear geographic grouping of Cuban isolates, virusgrowth and genetic diversity provide strong evidence of the PRSV dispersion patterns.